Translocation-dominated phytoextraction of cadmium and lead from contaminated agricultural soil by Ageratum conyzoides L. - An, The Huynh; Lien, Bich Ho (Journal of Degraded and Mining Lands Management, 2026)
Heavy metal contamination of agricultural soils, particularly cadmium (Cd) and lead (Pb), poses a serious threat to ecosystem integrity and food safety in rapidly urbanizing regions. This study evaluated the growth response, biomass production, metal accumulation, and translocation behavior of Ageratum conyzoides L. under varying Cd and Pb concentrations using a controlled pot experiment. Soil was amended with Cd and Pb at levels ranging from 0 to 800 mg/kg, and plant growth parameters, biomass distribution, metal uptake, bioconcentration factor (BCF), and translocation factor (TF) were systematically assessed after 60 days. The results showed that increasing Cd and Pb concentrations significantly inhibited plant growth and biomass production, particularly at higher contamination levels; however, Ageratum conyzoides L. maintained survival and metal uptake capacity throughout the experiment. Metal accumulation in plant tissues increased proportionally with soil contamination, with more than 80% of total Cd and Pb preferentially allocated to aboveground parts. Although BCF values for both metals were consistently below unity, TF values exceeded 1 across all treatments, indicating efficient root-to-shoot translocation. Specifically, 76.83 - 84.96 % of the accumulated Cd and Pb was partitioned into aboveground biomass, with translocation factor (TF) values ranging from 3.316 to 6.088 across all treatments. These findings suggest that Ageratum conyzoides L. exhibits a translocation-dominated accumulation strategy and holds considerable potential for phytoextraction of Cd- and Pb-contaminated soils, particularly under low to moderate pollution conditions.